Smart candy as a salivary pH indicator for early detection of dental caries risk in children with family-based preventive approach: A literature review - Zelka Dapala; Yana Nitya Safira; Videli Elvaretta; Muhammad Dwivo Doprecia; Inez Shafa Damhudi (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Dental caries is a multifactorial pathological condition and highly prevalent non-communicable disease, particularly in children, with significant impacts on health and quality of life. Early detection remains challenging due to invasive, clinic-based methods that are often inaccessible to children. This literature review aims to explore the potential of smart candy as a salivary pH indicator combined with a family-based preventive, offering a child-friendly and community-based strategy to support early caries prevention in alignment with national and global oral health goals. Methods: This study utilized a literature review method with the keywords “dental caries in children”, “family-based preventive”, and “smart candy [MeSH]” to explore databases such as Google Scholar, ScienceDirect, ResearchGate, and NCBI. Inclusion criteria included in vitro and in vivo experimental studies, cohort studies, comparative analysis studies, and reviews published in the last 10 years. Exclusion criteria included incomplete studies, inaccessible papers, and non-English or Indonesian texts. Based on these criteria, 50 references were selected including journals and books for review. Findings: Smart candy has shown the effectiveness as salivary pH-indicator tool that facilitates early detection of dental caries risk by providing real-time visual cues based on salivary pH changes. When integrated with a family-based approach, it helps overcome psychosocial barriers and improves adherence to preventive oral health behaviors in children. Conclusion: Smart candy is a child-friendly innovation that detects early dental caries through salivary pH-based visual cues, supporting preventive care and empowering families, especially in underserved areas. Despite challenges like regulation and supervision, government-backed community integration could boost its impact and support national and global oral health goals. Novelty/Originality of this article: This study explores smart candy as a child-friendly innovation for early caries detection. Combined with family-based prevention, it offers a new approach to reduce dental caries in children.